POST-VACCINATION IMMUNITY TO MEASLES IN CHILDREN WHO HAVE HAD COVID (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Patients with juvenile idiopathic arthritis (JIA) may have low protective levels of antibodies to vaccine antigens due to the immunologic features of the disease, disrupted vaccination schedules, and use of immunosuppressive medications.The purpose of the study was to study the state of post-vaccination immunity and determine the factors associated with the preservation of the protective level of antibodies in patients with JIA.